Maternal Age and Risk of Cesarean Section in Women With Induced Labor at Term—A Nordic Register-based Study. Issue 4 (December 2020) - Bergholt, T.; Skjeldestad, F.; Pyykönen, A.; Rasmussen, S.; Tapper, A.; Bjarnadóttir, R.; Smárason, A.; Másdóttir, B.; Klungsøyr, K.; Albrechtsen, S.; Källén, K.; Gissler, M.; et al.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:283–289) Following a decades-long upward trend of maternal age at childbirth, rates of labor induction (IOL) and cesarean deliveries (CDs) have also increased worldwide. Given those patterns, the authors of this study aimed to assess how maternal age and induction of labor impacted the rate of CD in both nulliparous and multiparous women.